2001
DOI: 10.1097/00000539-200107000-00039
|View full text |Cite
|
Sign up to set email alerts
|

The Antinociceptive Effect of the Combination of Spinal Morphine with Systemic Morphine or Buprenorphine

Abstract: Spinal morphine interacts with systemic morphine or buprenorphine in asupraadditive manner. This mode of interaction most probably results from the simultaneous activation of spinal and supraspinal antinociceptive systems. Supraspinal structures played a more important role in the antinociceptive effect of experimental combinations than structures of the spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 10 publications
3
38
0
2
Order By: Relevance
“…Thus, these overall results suggest multiple action sites of PcL. Because the hot plate is a specific central antinociceptive test in which opioid agents exert their analgesic effects via supra spinal and spinal receptors, 28) and considering the results of this study, the hot plate test was selected to be used to evaluate a possible central antinociception via supra spinal and spinal receptors for the PcL analgesic effect. Although morphine caused a significant increase in the latency for mice licking the paw when compared to the control group, PcL did not significantly modify the latencies compared to the saline or indomethacine controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, these overall results suggest multiple action sites of PcL. Because the hot plate is a specific central antinociceptive test in which opioid agents exert their analgesic effects via supra spinal and spinal receptors, 28) and considering the results of this study, the hot plate test was selected to be used to evaluate a possible central antinociception via supra spinal and spinal receptors for the PcL analgesic effect. Although morphine caused a significant increase in the latency for mice licking the paw when compared to the control group, PcL did not significantly modify the latencies compared to the saline or indomethacine controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 The antinociceptive effect of V. ashei extract was investigated by the standard Eddy's hot plate method 19 as a thermal pain experimental model. 31,32 Analysis of the data revealed a statistically significant difference in the hot plate reaction time between the test and the control groups (P < .05). Thus V. ashei exhibited a significant analgesic effect at the doses studied after 1 hour and after 21 days of administration.…”
Section: Discussionmentioning
confidence: 96%
“…Because the hot plate and tail flick tests both measure responses to thermal pain and often reflect central drug actions mediated by supraspinal and spinal mechanisms [26,27] , our results suggested that the antinociceptive effects of MB-1C-OH may occur via a peripheral-rather than a central-acting mechanism. We further evaluated the antinociception produced by MB-1C-OH using the acetic acid-induced writhing and formalin tests.…”
Section: Discussionmentioning
confidence: 83%